Metal-doped p-type nano bismuth titanate as well as preparation and application thereof

Preparation of metal-doped p-type bismuth titanate by solid phase mixing method solves the problems of cumbersome preparation methods and low reproducibility in the prior art, and achieves the effect of efficient industrial production and improving the activity of photohydrogen production by photolysis .

CN119430276AActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310965867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

In the prior art, the preparation method of metal-doped bismuth titanate is complicated, the reproducibility is not high, and it is difficult to achieve industrial and efficient production.

Method used

By solid phase mixing method, TiO2, Bi2O3 and the precursor doped metal are thoroughly wet-mixed, followed by vacuum drying and high temperature calcination to form metal-doped p-type bismuth titanate.

Benefits of technology

The metal-doped p-type bismuth titanate is achieved with simple controllability, good reproducibility and low cost, suitable for industrial and efficient production, and improves its activity in the process of photohydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004373501020000011
    Figure HDA0004373501020000011
Patent Text Reader

Abstract

The invention discloses metal-doped p-type nano bismuth titanate and a preparation method thereof, and belongs to the field of nano catalytic materials. The preparation method comprises the following steps: firstly, carrying out ball milling on titanium dioxide, bismuth oxide and a metal-doped precursor, fully mixing, then carrying out high-temperature calcination in a muffle furnace, and cooling to obtain the metal-doped p-type nano bismuth titanate. The method has the advantages of being simple, controllable, good in reproducibility, low in cost, suitable for industrial efficient production and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-catalytic material preparation, and in particular to a metal-doped p-type nano-bismuth titanate and a preparation method thereof. Background Art

[0002] As an emerging material among perovskite materials, bismuth titanate is currently widely used, including ferroelectric field effect transistors, photoelectric / photovoltaic conversion elements, thermoelectric materials, high-temperature piezoelectric ceramics, etc. The photoelectric / photovoltaic conversion and conductivity can be further enhanced by constructing n-type semiconductors through high-valent metal doping or constructing p-type semiconductors through low-valent metal doping.

[0003] The current methods for metal-doped bismuth titanate include high-frequency sputtering, radio frequency magnetron sputtering, sol-gel spin coating, and solid-phase mixing. The former processes are cumbersome and have low reproducibility, making them difficult to industrialize and efficiently produce. Relatively speaking, the solid-phase mixing method is a simple strategy. Currently, acrylic copolymer emulsions (Xianlin Dong et al., doi: 10.1016 / j.jeurceramsoc.2018.08.025) or polyvinyl alcohol emulsions (Shujun Zhang et al., doi: 10.1016 / j.jeurceramsoc.2018.12.061) are usually used as binders. The preparation process requires calcination, granulation, tableting, high-temperature decomposition of the binder, and re-ball milling, which is relatively cumbersome.

[0004] Therefore, there is an urgent need to develop a method for metal-doped p-type nano-bismuth titanate that is simple, efficient, reproducible, and suitable for industrial and efficient production. Summary of the invention

[0005] The purpose of the present invention is to provide a metal-doped p-type nano-bismuth titanate and a preparation method thereof, which has the advantages of being simple and controllable, having good reproducibility, low cost, and being suitable for industrialized and efficient production.

[0006] A method for preparing metal-doped p-type nano-bismuth titanate, the method comprising:

[0007] (1) Put TiO2, Bi2O3 and metal-doped precursors into a ball mill, add liquid grinding media, and wet grind and mix thoroughly;

[0008] (2) vacuum drying the ball-milled slurry to remove the liquid, collecting the obtained powder sample and grinding it into a powder sample with a mortar;

[0009] (3) The powder sample is placed in a crucible and calcined at high temperature in an air atmosphere muffle furnace, and after cooling, metal-doped p-type nano-bismuth titanate is obtained.

[0010] Preferably, the TiO2 in step (1) is anatase phase and / or rutile phase; the molar ratio of TiO2 to Bi2O3 is 3:1 to 1:20, preferably 3:1 to 3:2; the metal-doped precursor is one or more of a doped metal carbonate, a doped metal bicarbonate, and a doped metal acetate; the doped metal is one or more of Sr, Ba, Ca, Y, Zn, Cd, Co, Ni, Pb, etc., whose atomic radius is smaller than Bi and whose valence is divalent and / or monovalent; the molar amount of the doped metal is 0.1 to 10.0 relative to bismuth titanate. %, preferably 0.1-5.0%; the liquid grinding medium is one or more of water, methanol and ethanol; the ratio of the volume of the solvent to the mass of the ball-milled material (the sum of TiO2, Bi2O3 and metal-doped precursors) is 0.5-3.0 mL / g, preferably 1.0-2.0 mL / g; the ball milling speed is 200-800 rpm / min, preferably 300-600 rpm / min; the ball milling time is 12-72 h, preferably 36-48 h; the material of the ball mill is one or more of materials with high hardness such as agate and zirconia.

[0011] Preferably, the drying temperature in step (2) is 60 to 100° C., preferably 60 to 80° C.; the drying time is 12 to 36 hours, preferably 18 to 24 hours.

[0012] Preferably, the material of the crucible in step (3) is alumina and / or quartz; the calcination temperature of the muffle furnace is 400-1100°C, preferably 600-800°C; the calcination time is 1-12h, preferably 2-6h; the heating rate from room temperature to the calcination temperature is 2-10°C / min, preferably 5-10°C / min.

[0013] The preparation principle of the metal-doped p-type nano-bismuth titanate provided by the present invention is as follows: TiO2, Bi2O3 and the metal-doped precursor are fully mixed and then gradually melted in a muffle furnace as the temperature rises, the metal-doped precursor salt decomposes, and the three components are evenly mixed. When the temperature is higher than 650°C, a new phase Bi4Ti3O 12 The low-valent metal partially replaces the position of Bi because its atomic radius is smaller than Bi and its valence is lower than Bi. 3+ (like Ba 2+ 、Zn 2+ ) will form local electron-deficient Lewis acidic sites, accompanied by the generation of a small amount of oxygen vacancies. For example, in photocatalytic reactions, photogenerated electrons are induced to migrate rapidly to the surface, which is a typical p-type semiconductor.

[0014] Compared with the prior art, the present invention has the following unique advantages:

[0015] (1) The present invention constructs metal-doped p-type nano-bismuth titanate by a solid-phase mixing method using a metal doping strategy with a low valence and an atomic radius smaller than Bi; the doped metal and its surrounding environment form new catalytic active sites.

[0016] (2) The metal-doped p-type nano-bismuth titanate described in the present invention is a multiphase catalytic material, which can be applied to processes such as photolysis of water to produce hydrogen, and can be recovered and recycled.

[0017] (3) The preparation method of the metal-doped p-type nano-bismuth titanate described in the present invention is simple and controllable, has good reproducibility, low cost, and is suitable for industrial and efficient production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD diagram of 2.0 mol % Ba-doped p-type nano-bismuth titanate obtained in Example 1. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not limit the scope of the present invention. The experimental schemes in the following embodiments that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0020] Example 1

[0021] 2.0 mol% Ba-doped p-type nano-bismuth titanate is obtained by the following process: first, 6 mmol TiO2 (anatase phase), 4 mmol Bi2O3 and 2.0 mol% barium carbonate relative to the molar amount of Bi are placed in an agate ball mill, 3 mL of water is added, and after sealing with a cover, the rotation speed is 400 rpm / min, and the wet grinding and mixing are fully carried out for 48 hours. Subsequently, the ball-milled slurry is vacuum dried at 80°C for 24 hours to remove the liquid, and the obtained powder sample is collected and fully ground with a mortar for 10 minutes. Finally, the powder sample is spread flat in an alumina crucible and calcined at 750°C in an air atmosphere muffle furnace for 2 hours (the heating rate from room temperature to the calcination temperature is 5°C / min). After cooling to room temperature, simple grinding is performed to obtain 2.0 mol% Ba-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Ba 2.0 -Bi4Ti3O 12 .

[0022] XRD test results show that the main crystal phase of the prepared Ba-doped p-type nano-bismuth titanate is Bi4Ti3O 12 (A recognized p-type semiconductor, reference: doi:

[0023] 10.1002 / adfm.201303214, the same below), Ba doping will form a small amount of new crystal phase BaBi4Ti4O 15 .

[0024] The reaction evaluation is shown in Application Example 1 and Comparative Example 1.

[0025] Example 2

[0026] 1.0 mol% Sr-doped p-type nano-bismuth titanate is obtained by the following process: first, 6 mmol TiO2 (rutile phase), 4 mmol Bi2O3 and 1.0 mol% strontium acetate relative to the molar amount of Bi are placed in a zirconia ball mill, 3 mL of water is added, and after sealing with a cover, the rotation speed is 400 rpm / min, and the wet grinding is fully mixed for 48 hours. Subsequently, the ball-milled slurry is vacuum dried at 80°C for 24 hours to remove the liquid, and the obtained powder sample is collected and fully ground with a mortar for 10 minutes. Finally, the powder sample is spread flat in a quartz crucible and calcined at 600°C in an air atmosphere muffle furnace for 2 hours (the heating rate from room temperature to the calcination temperature is 5°C / min). After cooling to room temperature, simple grinding is performed to obtain 1.0 mol% Sr-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Sr 1.0 -Bi4Ti3O 12 .

[0027] XRD test results show that the main crystal phase of the prepared Sr-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Sr doping will form a small amount of new crystal phase Sr2Bi4Ti5O 18 .

[0028] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 97.2 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 4 times, indicating that Sr 1.0 -Bi4Ti3O 12 Successfully prepared.

[0029] Example 3

[0030] 5.0 mol% Ca-doped p-type nano-bismuth titanate was obtained by the following process: First, 6 mmol TiO2 (anatase phase), 4 mmol Bi2O3 and 5.0 mol% calcium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3 mL of ethanol was added, and after sealing with a cover, the speed was 600 rpm / min, and the wet grinding was fully mixed for 36 hours. Subsequently, the ball-milled slurry was vacuum dried at 60°C for 18 hours to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10 minutes. Finally, the powder sample was spread flat in an alumina crucible and calcined at 900°C in an air atmosphere muffle furnace for 1 hour (the heating rate from room temperature to the calcination temperature was 10°C / min). After cooling to room temperature, 5.0 mol% Ca-doped p-type nano-bismuth titanate relative to the molar amount of Bi was obtained by simple grinding, with a particle size of 10 to 100 nm, marked as Ca. 5.0 -Bi4Ti3O 12 .

[0031] XRD test results show that the main crystal phase of the prepared Ca-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Ca doping will form a small amount of new crystalline phase CaTiO3.

[0032] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 92.2 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 4 times, indicating that Ca 5.0 -Bi4Ti3O 12 Successfully prepared.

[0033] Example 4

[0034] 0.5 mol% Cd-doped p-type nano-bismuth titanate was obtained by the following process: First, 6 mmol TiO2 (rutile phase), 4 mmol Bi2O3 and 0.5 mol% cadmium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 1 mL of methanol was added, and after sealing with a cover, the speed was 400 rpm / min, and the wet grinding was fully mixed for 48 hours. Subsequently, the ball-milled slurry was vacuum dried at 60°C for 18 hours to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10 minutes. Finally, the powder sample was spread flat in an alumina crucible and calcined at 500°C in an air atmosphere muffle furnace for 6 hours (the heating rate from room temperature to the calcination temperature was 5°C / min). After cooling to room temperature, simple grinding was performed to obtain 0.5 mol% Cd-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Cd 0.5-Bi4Ti3O 12 .

[0035] XRD test results show that the main crystal phase of the prepared Cd-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Cd doping will form a small amount of new crystalline phase CdTiO3.

[0036] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 157.8 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 7 times, indicating that Cd 0.5 -Bi4Ti3O 12 Successfully prepared.

[0037] Example 5

[0038] 1.0 mol% Ni-doped p-type nano-bismuth titanate was obtained by the following process: first, 6 mmol TiO2 (anatase phase), 4 mmol Bi2O3 and 1.0 mol% cadmium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3 mL of methanol was added, and after sealing with a cover, the speed was 400 rpm / min, and the wet grinding was fully mixed for 48 hours. Subsequently, the ball-milled slurry was vacuum dried at 60°C for 18 hours to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10 minutes. Finally, the powder sample was spread flat in an alumina crucible and calcined at 750°C in an air atmosphere muffle furnace for 2 hours (the heating rate from room temperature to the calcination temperature was 5°C / min). After cooling to room temperature, simple grinding was performed to obtain 1.0 mol% Ni-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Ni. 1.0 -Bi4Ti3O 12 , Ni doping will form a small amount of new crystalline phase NiTiO3.

[0039] XRD test results show that the main crystal phase of the prepared Ni-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Ni doping will form a small amount of new crystalline phase NiTiO3.

[0040] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 160.1 μmol g -1 h -1Compared with Comparative Example 1, the hydrogen yield increased by about 7 times, indicating that Ni 1.0 -Bi4Ti3O 12 Successfully prepared.

[0041] Example 6

[0042] 3.0 mol% Co-doped p-type nano-bismuth titanate was obtained by the following process: first, 6 mmol TiO2 (anatase phase), 4 mmol Bi2O3 and 3.0 mol% cobalt acetate relative to the molar amount of Bi were placed in an agate ball mill, 3 mL of water was added, and after sealing with a cover, the rotation speed was 400 rpm / min, and the wet grinding and mixing were fully carried out for 48 hours. Subsequently, the ball-milled slurry was vacuum dried at 80°C for 24 hours to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10 minutes. Finally, the powder sample was spread flat in an alumina crucible and calcined at 750°C in an air atmosphere muffle furnace for 2 hours (the heating rate from room temperature to the calcination temperature was 5°C / min). After cooling to room temperature, simple grinding was performed to obtain 3.0 mol% Co-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Co. 3.0 -Bi4Ti3O 12 .

[0043] XRD test results show that the main crystal phase of the prepared Co-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Co doping will form a small amount of new crystalline phase CoTiO3.

[0044] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 70.9 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 3 times, indicating that Co 3.0 -Bi4Ti3O 12 Successfully prepared.

[0045] Example 7

[0046] 1.5 mol% Pb-doped p-type nano-bismuth titanate was obtained by the following process: First, 6 mmol TiO2 (rutile phase), 4 mmol Bi2O3 and 1.5 mol% lead carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3 mL of water was added, and after sealing with a cover, the speed was 400 rpm / min, and the wet grinding was fully mixed for 48 hours. Subsequently, the ball-milled slurry was vacuum dried at 80°C for 24 hours to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10 minutes. Finally, the powder sample was spread flat in an alumina crucible and calcined at 700°C in an air atmosphere muffle furnace for 2.5 hours (the heating rate from room temperature to the calcination temperature was 5°C / min). After cooling to room temperature, simple grinding was performed to obtain 1.5 mol% Pb-doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Pb 1.5 -Bi4Ti3O 12 .

[0047] XRD test results show that the main crystal phase of the prepared Pb-doped p-type nano-bismuth titanate is Bi4Ti3O 12 , Pb doping will form a small amount of new crystalline phase PbBi4Ti4O 15 .

[0048] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 98.4 μmol g -1 h -1 Compared with comparative example 1, the hydrogen yield increased by about 4 times, indicating that Pb 1.5 -Bi4Ti3O 12 Successfully prepared.

[0049] Example 8

[0050] 1.0mol% Pb and 1.0mol% Ba doped p-type nano-bismuth titanate was obtained by the following process: First, 6mmol TiO2 (rutile phase), 4mmol Bi2O3 and 1.0mol% lead carbonate and 1.0mol% barium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3mL of water was added, and after sealing with a cover, the speed was 400rpm / min, and the wet grinding was fully mixed for 48h. Subsequently, the ball-milled slurry was vacuum dried at 80℃ for 24h to remove the liquid, and the obtained powder sample was collected and fully ground with a mortar for 10min. Finally, the powder sample was spread flat in an alumina crucible and calcined at 750℃ in an air atmosphere muffle furnace for 2h (the heating rate from room temperature to the calcination temperature was 5℃ / min). After cooling to room temperature, simple grinding was performed to obtain 1.0mol% Pb and 1.0mol% Ba doped p-type nano-bismuth titanate relative to the molar amount of Bi, with a particle size of 10 to 100nm, marked as Pb 1.0 Ba 1.0 -Bi4Ti3O 12 , the doping of Pb and Ba will form a small amount of new crystalline phase PbBi4Ti4O 15 and BaBi4Ti4O 15 .

[0051] XRD test results show that the main crystal phase of the prepared Pb and Ba doped p-type nano-bismuth titanate is Bi4Ti3O 12 .

[0052] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 195.6 μmol g -1 h -1 Compared with comparative example 1, the hydrogen yield increased by about 8 times, indicating that Pb 1.0 Ba 1.0 -Bi4Ti3O 12 Successfully prepared.

[0053] Example 9

[0054] 0.5mol% Sr, 0.5mol% Ba and 0.5mol% Cd doped p-type nano-bismuth titanate was obtained by the following process: first, 6mmol TiO2 (rutile phase), 4mmol Bi2O3 and 0.5mol% strontium carbonate, 0.5mol% barium carbonate and 0.5mol% cadmium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3mL of water was added, and after sealing with a cover, the speed was 400rpm / min, and the wet grinding was fully mixed for 48h. The ball-milled slurry was then vacuum dried at 80℃ for 24h to remove the liquid, and the powder sample was collected and fully ground with a mortar for 10min. Finally, the powder sample was spread in an alumina crucible and calcined at 750℃ in an air atmosphere muffle furnace for 2h (the heating rate from room temperature to the calcination temperature was 5℃ / min). After cooling to room temperature, simple grinding was performed to obtain p-type nano-bismuth titanate doped with 0.5 mol% Sr, 0.5 mol% Ba and 0.5 mol% Cd relative to the molar amount of Bi, with a particle size of 10 to 100 nm, marked as Sr 0.5 Ba 0.5 Cd 0.5 -Bi4Ti3O 12 .

[0055] XRD test results show that the main crystal phase of the prepared Sr, Ba and Cd doped p-type nano-bismuth titanate is Bi4Ti3O 12 The doping of Sr, Ba and Cd will form a small amount of new crystal phase Sr2Bi4Ti5O 18 、BaBi4Ti4O 15 and CdTiO3.

[0056] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 173.2 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 7 times, indicating that Sr 0.5 Ba 0.5 Cd 0.5 -Bi4Ti3O 12 Successfully prepared.

[0057] Example 10

[0058] 0.5mol% Sr and 1.0mol% Cd doped p-type nano-bismuth titanate was obtained by the following process: first, 6mmol TiO2 (anatase phase), 4mmol Bi2O3 and 0.5mol% strontium carbonate and 1.0mol% cadmium carbonate relative to the molar amount of Bi were placed in an agate ball mill, 3mL of water was added, the cover was sealed, and the speed was 400rpm / min, and the wet grinding was fully mixed for 48h. Then the ball-milled slurry was vacuum dried at 80℃ for 24h to remove the liquid, and the powder sample was collected and fully ground with a mortar for 10min. Finally, the powder sample was spread flat in an alumina crucible and calcined at 750℃ in an air atmosphere muffle furnace for 2h (the heating rate from room temperature to the calcination temperature was 5℃ / min). After cooling to room temperature, simple grinding was performed to obtain p-type nano-bismuth titanate doped with 0.5mol% Sr and 1.0mol% Cd relative to the molar amount of Bi, with a particle size of 10 to 100nm, marked as Sr 0.5 Cd 1.0 -Bi4Ti3O 12 , Sr and Cd doping will form a small amount of new crystal phase Sr2Bi4Ti5O 18 and CdTiO3.

[0059] XRD test results show that the main crystal phase of the prepared Sr and Cd doped p-type nano-bismuth titanate is Bi4Ti3O 12 .

[0060] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 146.9 μmol g -1 h -1 Compared with Comparative Example 1, the hydrogen yield increased by about 6 times, indicating that Sr 0.5 Cd 1.0 -Bi4Ti3O 12 Successfully prepared.

[0061] Application Example 1

[0062] Take 10 mg of Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was added to 1.0 ml of an aqueous solution containing 20% ​​methanol by volume. After removing the oxygen in the system, an 18W UV LED lamp was turned on and the photocatalytic reaction was carried out for 3 hours under the condition of a UV light source of 365 nm. After the reaction, He was added as an internal standard to quantify the generated hydrogen. Gas chromatography analysis showed that the yield of hydrogen was 127.8 μmol g -1 h -1 .

[0063] Comparative Example 1

[0064] Take 10 mg of Bi4Ti3O prepared in the same manner as in Example 1 but without metal doping 12 The catalyst was added to 1.0 ml of an aqueous solution containing 20% ​​methanol by volume. After removing the oxygen in the system, an 18W UV LED lamp was turned on and the photocatalytic reaction was carried out for 3 hours under the condition of a UV light source of 365 nm. After the reaction, He was added as an internal standard to quantify the hydrogen produced. Gas chromatography analysis showed that the yield of hydrogen was 23.1 μmol g -1 h -1 .

[0065] The results show that by constructing metal-doped p-type nano-bismuth titanate Ba 2.0 -Bi4Ti3O 12 It can significantly improve the effect of photolysis of water to produce hydrogen, compared with Bi4Ti3O without metal doping 12 , the active hydrogen yield increased by about 5 times. 2.0 -Bi4Ti3O 12 The p-type nano-bismuth titanate was successfully prepared. It constructed doping energy levels and surface active sites through metal doping, promoted the separation of photogenerated carriers, and improved the activity of photocatalytic water splitting to produce hydrogen.

Claims

1. A method for preparing metal-doped p-type nano-bismuth titanate, characterized in that: The method comprises: (1) TiO2, Bi2O3 and metal-doped precursors are placed in a ball mill, liquid grinding media is added, and wet-milling is performed to mix them thoroughly; the metal-doped precursor is one or more of Sr, Ba, Ca, Y, Zn, Cd, Co, Ni, and Pb; (2) vacuum drying the ball-milled slurry to remove the liquid, collecting the obtained powder sample and grinding it into a powder sample with a mortar; (3) The powder sample is placed in a crucible and calcined at high temperature in an air atmosphere muffle furnace, and after cooling, metal-doped p-type nano-bismuth titanate is obtained.

2. The method according to claim 1, characterized in that In step (1), the TiO2 is in anatase phase and / or rutile phase; the molar ratio of TiO2 to Bi2O3 is 3:1 to 1:20, preferably 3:1 to 3:

2.

3. The method according to claim 1, characterized in that In step (1), the precursor of the doped metal is one or more of a doped metal carbonate, a doped metal bicarbonate, and a doped metal acetate; the doped metal is one or more of Sr, Ba, Ca, Y, Zn, Cd, Co, Ni, Pb, etc., whose atomic radius is smaller than Bi and whose valence is divalent and / or monovalent; the molar amount of the doped metal is 0.1-10.0% relative to bismuth titanate, preferably 0.1-5.0%.

4. The method according to claim 1, characterized in that: In step (1), the liquid grinding medium is one or more of water, methanol, and ethanol; the ratio of the volume of the solvent to the mass of the ball-milled material (the sum of TiO2, Bi2O3 and metal-doped precursors) is 0.5 to 3.0 mL / g, preferably 1.0 to 2.0 mL / g.

5. The method according to claim 1, characterized in that In step (1), the ball milling speed is 200 to 800 rpm / min, preferably 300 to 600 rpm / min; the ball milling time is 12 to 72 h, preferably 36 to 48 h.

6. The method according to claim 1, characterized in that In step (2), the drying temperature is 60 to 100° C., preferably 60 to 80° C.; the drying time is 12 to 36 hours, preferably 18 to 24 hours.

7. The method according to claim 1 or 5, characterized in that: In step (1), the material of the ball mill is one or more of materials with high hardness such as agate and zirconia; In step (3), the crucible is made of alumina and / or quartz.

8. The method according to claim 1, characterized in that In step (3), the muffle furnace calcination temperature is 400-1100°C, preferably 600-800°C; the calcination time is 1-12h, preferably 2-6h; the heating rate from room temperature to the calcination temperature is 2-10°C / min, preferably 5-10°C / min.

9. A metal-doped p-type nano-bismuth titanate prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the metal-doped p-type nano-bismuth titanate according to claim 9 in a process of catalytic photolysis of water to produce hydrogen.

Citation Information

Patent Citations

  • Preparation method for low-loss and high-resistivity Bi4Ti3O12-based lead-free piezoelectric ceramics

    CN104402433A

  • Y-element doped titanium bismuth ferrite multiferroic ceramic material of Aurivillius phase structure and preparation method thereof

    CN109678491A